Experiences about self-care of mothers of children with microcephaly due to congenital Zika syndrome (Research, Society and Development, 2022)
Objective: To understand the experiences about self-care by mothers of children with microcephaly due to congenital Zika syndrome. Methodology: This is an exploratory, qualitative and phenomenological study, carried out in two health units in the State of Pernambuco, with seven mothers of children with microcephaly due to congenital Zika syndrome, through semi-structured interviews guided by a script, recorded and transcribed. in full and analyzed by the technique of content analysis in the Heideggerian perspective. Results: The analysis of the interviews allowed the identification of the following units of meaning: “Being a mother of a child with microcephaly” and “The new way of being-in-the-world: implications for self-care”. Conclusion: It was found that mothers of children with microcephaly due to congenital Zika syndrome are overloaded with activities, leading to a lack of care for their health and appearance, as well as a poor quality of life. New studies are proposed so that these women are recognized as beings who also need care.